Pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, and optical member
The problem of floating or peeling of the adhesive layer on the curved display device is solved by achieving a balance between initial light peelability and high adhesive strength in the manufacturing of the display device by a specific composition of the pressure-sensitive adhesive composition and copolymer, and is suitable for optical components.
Patent Information
- Application Number
- JP2021021945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-15
- Publication Date
- 2025-02-06
- Estimated Expiration
- 2041-02-15
AI Technical Summary
The prior art is difficult to achieve a balance between initial light peelability and high bond strength during the manufacturing process of display equipment, especially in curved display equipment, where the bonding layer is prone to floating or peeling problems.
A pressure-sensitive adhesive composition with a specific composition, comprising a copolymer of a (meth)acrylic polymer with a low glass transition temperature and an organosiloxane framework, is used to achieve a balance of initial light peelability and high bond strength by adjusting its uneven distribution on the surface of the adhesive.
It exhibits light peeling properties during initial bonding and maintains high bonding strength after heating, suitable for curved display devices and optical components with uneven surfaces, avoiding the adhesive layer floating or peeling.
Smart Images

Figure 0007627574000001 
Figure 0007627574000002 
Figure 0007627574000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet, and an optical member. [Background technology]
[0002] Pressure-sensitive adhesive compositions used in various display devices are required to be able to form a pressure-sensitive adhesive layer that exhibits easy peelability at the initial stage of lamination and high adhesive strength after heating. In response to such requirements, various pressure-sensitive adhesive compositions have been developed.
[0003] For example, Patent Document 1 discloses a pressure-sensitive adhesive composition comprising 100 parts by mass of a polymer (A) having a glass transition temperature of less than 0° C., and 0.1 to 20 parts by mass of a copolymer (B) having a weight average molecular weight in the range of 10,000 or more and less than 100,000, the copolymer including, as monomer units, a monomer having an organosiloxane skeleton and a functional group equivalent in the range of 1,000 g / mol or more and less than 15,000 g / mol, and a monomer having a homopolymer glass transition temperature of 40° C. or more. Furthermore, for example, Patent Document 2 discloses a pressure-sensitive adhesive composition comprising 100 parts by mass of a polymer (A) having a glass transition temperature of less than 0°C, and 0.1 to 20 parts by mass of a copolymer (B) having a weight average molecular weight of 10,000 or more and less than 100,000, the copolymer (B) comprising, as monomer units, a monomer (B1) having an organosiloxane skeleton and a functional group equivalent in the range of 1,000 g / mol or more and 4,600 g / mol or less, and a monomer (B2) having a homopolymer glass transition temperature of 40°C or more, wherein the copolymer (B) is a copolymer containing 10% by mass to 20% by mass of monomer (B1) and 30% by mass to 50% by mass of monomer (B2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2015 / 163115 [Patent Document 2] JP 2017-203164 A Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, in the manufacture of various display devices, after various members are attached to an adherend via an adhesive layer, they may be transported, stored, etc., and may take time before moving to the next process. Therefore, the adhesive layer applied to various display devices is required to have a light peelability that is unlikely to deteriorate over time at the initial stage of attachment. In recent years, with the diversification of consumer tastes, various display devices are required to have high design quality, and the shapes of displays are becoming more diverse, such as displays with curved shapes being distributed on the market. However, for example, when an adhesive layer is attached to a display with a curved shape, problems such as lifting and peeling of the adhesive layer are likely to occur. For this reason, adhesive layers used in various display devices are required to exhibit easy peelability from the adherend in the initial stage of attachment and high adhesive strength after heating, as well as to be resistant to loss of the easy peelability exhibited in the initial stage of attachment over time and to have good compatibility with the adherend.
[0006] An object of one embodiment of the present disclosure is to provide a pressure-sensitive adhesive composition that exhibits easy releasability at the initial stage of application, that is unlikely to lose this easy releasability over time, that exhibits high adhesive strength after heating, and that is capable of forming a pressure-sensitive adhesive layer that has good compatibility with an adherend. The problem that another embodiment of the present disclosure aims to solve is to provide a pressure-sensitive adhesive sheet having an adhesive layer that exhibits easy releasability at the initial stage of application, is unlikely to lose this easy releasability over time, exhibits high adhesive strength after heating, and has good compatibility with an adherend. Another problem that another embodiment of the present disclosure aims to solve is to provide an optical component having a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of bonding, is unlikely to lose this easy releasability over time, exhibits high adhesive strength after heating, and has good compatibility with an adherend. [Means for solving the problem]
[0007] Specific means for solving the problems include the following aspects. <1> A (meth)acrylic polymer (A) containing a structural unit derived from a monomer having a crosslinkable functional group and having a glass transition temperature of less than 0°C; a (meth)acrylic copolymer (B) containing 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, relative to all structural units, and 25% by mass to 45% by mass of structural units derived from a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or higher and lower than 10°C when made into a homopolymer, and having a weight average molecular weight of 40,000 to 400,000; A cross-linking agent; Including, the number average molecular weight of the monomer having an organosiloxane skeleton in the (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000; A pressure-sensitive adhesive composition, wherein the content of the (meth)acrylic copolymer (B) is 0.1 to 21 parts by mass relative to 100 parts by mass of the (meth)acrylic polymer (A).
[0008] <2> The monomer having an organosiloxane skeleton is a compound represented by the following formula (1): <1> The pressure-sensitive adhesive composition according to claim 1.
[0009] [ka]
[0010] In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a monovalent organic group. m and n each independently represent 0 or an integer of 1 or more, provided that m and n are not 0 at the same time.
[0011] <3> <1> or <2> A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1. <4> <1> or <2> An optical member comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1. Effect of the Invention
[0012] According to one embodiment of the present disclosure, there is provided a pressure-sensitive adhesive composition which exhibits easy releasability at the initial stage of application, which is unlikely to lose this easy releasability over time, which exhibits high adhesive strength after heating, and which is capable of forming a pressure-sensitive adhesive layer which has good compatibility with an adherend. According to another embodiment of the present disclosure, there is provided a pressure-sensitive adhesive sheet having an adhesive layer that exhibits easy releasability at the initial stage of application, that is unlikely to lose this easy releasability over time, that exhibits high adhesive strength after heating, and that has good compatibility with an adherend. In addition, according to another embodiment of the present disclosure, there is provided an optical component having a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of bonding, that is unlikely to lose this easy releasability over time, that exhibits high adhesive strength after heating, and that has good compatibility with an adherend. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, and optical member of the present disclosure will be described in detail below. The following description of the requirements may be based on a representative embodiment of the present disclosure, but the present disclosure is not limited to such an embodiment, and can be modified as appropriate within the scope of the purpose of the present disclosure.
[0014] In the present disclosure, a numerical range indicated using "to" means a range that includes the numerical values before and after "to" as the lower limit and upper limit, respectively. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in the present disclosure. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.
[0015] In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In the present disclosure, when the adhesive composition contains multiple substances corresponding to each component, the amount of each component in the adhesive composition means the total amount of the multiple substances present in the adhesive composition, unless otherwise specified.
[0016] In the present disclosure, the term "(meth)acrylic (co)polymer" refers to a (co)polymer in which the content of structural units derived from a monomer having a (meth)acryloyl group is 50% by mass or more of all structural units (i.e., all structural units of the (meth)acrylic (co)polymer). Here, the term "(co)polymer" refers to a polymer or a copolymer. In the present disclosure, "(meth)acrylic monomer" means a monomer having a (meth)acryloyl group.
[0017] In this disclosure, "(meth)acrylic" is a term that encompasses both "acrylic" and "methacrylic", "(meth)acrylate" is a term that encompasses both "acrylate" and "methacrylate", and "(meth)acryloyl" is a term that encompasses both "acryloyl" and "methacryloyl".
[0018] In this disclosure, "n-" means normal, "i-" means iso, "s-" means secondary, and "t-" means tertiary.
[0019] In the present disclosure, "after heating" means, for example, after a temperature of 50° C. or more is applied. The upper limit of the temperature is, for example, 300° C.
[0020] In the present disclosure, the specific (meth)acrylic polymer (A) and the specific (meth)acrylic copolymer (B) are collectively referred to as "specific (meth)acrylic polymer".
[0021] [Adhesive composition] The pressure-sensitive adhesive composition of the present disclosure comprises a (meth)acrylic polymer (A) (hereinafter also referred to as "specific (meth)acrylic polymer (A)") which contains structural units derived from a monomer having a crosslinkable functional group and has a glass transition temperature of less than 0°C, and a (meth)acrylic copolymer (B) (hereinafter also referred to as "specific (meth)acrylic copolymer (B)") which contains 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, relative to all structural units, and 25% by mass to 45% by mass of structural units derived from a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or more and less than 10°C, relative to all structural units, and has a weight average molecular weight of 40,000 to 400,000. and a crosslinking agent, wherein the number average molecular weight of the monomer having an organosiloxane skeleton in the (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000, and the content of the (meth)acrylic copolymer (B) is 0.1 to 21 parts by mass per 100 parts by mass of the (meth)acrylic polymer (A). The pressure-sensitive adhesive composition of the present disclosure can form a pressure-sensitive adhesive layer that exhibits easy releasability at the initial stage of application, is unlikely to lose this easy releasability over time, and exhibits high adhesive strength after heating, as well as good compatibility with the adherend. The reason why the pressure-sensitive adhesive composition of the present disclosure can exhibit such an effect is unclear, but the present inventors speculate as follows, however, the following speculation is not intended to limit the pressure-sensitive adhesive composition of the present disclosure, but is merely an example.
[0022] The monomer having an organosiloxane skeleton has a low polarity derived from its structure, and therefore tends to cause the specific (meth)acrylic copolymer (B) to be unevenly distributed on the adhesive surface of the pressure-sensitive adhesive layer. Here, the "adhesive surface of the pressure-sensitive adhesive layer" may be, for example, the interface between the pressure-sensitive adhesive layer and the adherend. In the pressure-sensitive adhesive composition of the present disclosure, by adjusting the content of constituent units derived from a monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B), the number average molecular weight of the monomer having an organosiloxane skeleton, and the content ratio of the specific (meth)acrylic copolymer (B) to the specific (meth)acrylic polymer (A), it is possible to appropriately unevenly distribute the specific (meth)acrylic copolymer (B) on the adhesive surface of the pressure-sensitive adhesive layer. It is presumed that the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure exhibits easy peelability from the adherend in the early stages of attachment because the specific (meth)acrylic copolymer (B) is appropriately unevenly distributed on the adhesive surface.
[0023] In addition, in the pressure-sensitive adhesive composition of the present disclosure, by adjusting the monomer composition, physical properties, etc. of the specific (meth)acrylic polymer (A) and the specific (meth)acrylic copolymer (B), appropriate uneven distribution of the specific (meth)acrylic copolymer (B) on the adhesive surface of the pressure-sensitive adhesive layer is maintained and the hardness of the adhesive surface of the pressure-sensitive adhesive layer is adjusted. It is presumed that the adhesive layer formed by the adhesive composition of the present disclosure maintains a moderate uneven distribution of the specific (meth)acrylic copolymer (B) on the adhesive surface, and therefore the light peelability at the initial stage of lamination is unlikely to be impaired over time. In addition, it is presumed that the adhesive layer formed by the adhesive composition of the present disclosure maintains a moderate uneven distribution of the specific (meth)acrylic copolymer (B) on the adhesive surface, and the adhesive surface does not become excessively hard, and therefore the adhesive layer exhibits high adhesive strength after heating and has good compatibility with the adherend.
[0024] In contrast to the pressure-sensitive adhesive composition of the present disclosure, the pressure-sensitive adhesive compositions described in Patent Document 1 (International Publication No. 2015 / 163115; hereinafter the same) and Patent Document 2 (JP Patent Publication No. 2017-203164; hereinafter the same) contain a relatively large amount of structural units derived from a monomer that has a relatively high glass transition temperature when made into a homopolymer, in the copolymer (B), which is considered to harden the adhesive surface of the pressure-sensitive adhesive layer with the adherend. For this reason, it is presumed that the pressure-sensitive adhesive layers formed by the pressure-sensitive adhesive compositions described in Patent Documents 1 and 2 have poor compatibility with the adherend.
[0025] The pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure can exhibit sufficiently high adhesive strength even when heated at a lower temperature (50°C) than conventional temperatures (approximately 70°C).
[0026] [Specific (meth)acrylic polymer (A)] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic polymer (A) [i.e., specific (meth)acrylic polymer (A)] which contains a constituent unit derived from a monomer having a crosslinkable functional group and has a glass transition temperature of less than 0°C.
[0027] <Structural Unit Derived from Monomer Having Crosslinkable Functional Group> The specific (meth)acrylic polymer (A) contains a constituent unit derived from a monomer having a crosslinkable functional group. The crosslinkable functional group of the constitutional unit derived from a monomer having a crosslinkable functional group can contribute to crosslinking with a crosslinking agent described below.
[0028] In the present disclosure, the term "structural unit derived from a monomer having a crosslinkable functional group" refers to a structural unit formed by addition polymerization of a monomer having a crosslinkable functional group.
[0029] An example of a monomer having a crosslinkable functional group is a monomer having at least one crosslinkable functional group and an ethylenically unsaturated group in one molecule. The type of the ethylenically unsaturated group is not particularly limited. Specific examples of the ethylenically unsaturated group include a vinyl group, an allyl group, a vinylphenyl group, a (meth)acrylamide group, and a (meth)acryloyl group. The ethylenically unsaturated group is preferably a (meth)acryloyl group.
[0030] The type of crosslinkable functional group is not particularly limited. Specific examples of the crosslinkable functional group include a hydroxyl group, a carboxyl group, and an amino group. The term "amino group" as used herein refers to a primary amino group and / or a secondary amino group. The crosslinkable functional group is preferably at least one of a hydroxyl group and a carboxy group.
[0031] The type of the monomer having a hydroxyl group is not particularly limited. Specific examples of monomers having a hydroxyl group include 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, and 1,1-dimethyl-3-hydroxybutyl (meth)acrylate. butyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, glycerin mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate. As the monomer having a hydroxyl group, for example, from the viewpoint of good copolymerizability with other monomers, hydroxyalkyl(meth)acrylates are preferred, and from the viewpoint of good compatibility with other monomers and good reactivity with crosslinking agents (particularly isocyanate-based crosslinking agents), hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 1 to 5 carbon atoms are more preferred, hydroxyalkyl(meth)acrylates having a hydroxyalkyl group with 2 to 4 carbon atoms are even more preferred, and 2-hydroxyethyl acrylate (2HEA) is particularly preferred.
[0032] The type of the monomer having a carboxy group is not particularly limited. Specific examples of monomers having a carboxy group include acrylic acid (AA), methacrylic acid (MAA), and crotonic acid. ,MaExamples of the vinyl esters include leic acid, fumaric acid, itaconic acid, glutaconic acid, citraconic acid, ω-carboxy-polycaprolactone mono(meth)acrylates (e.g., ω-carboxy-polycaprolactone (n≒2) monoacrylate), succinic acid esters (e.g., 2-acryloyloxyethyl-succinic acid), vinyl formate, vinyl acetate, vinyl propionate, and vinyl neodecanoate. As the monomer having a carboxy group, for example, acrylic acid (AA) is preferred from the viewpoint of good reactivity with a crosslinking agent (particularly, an isocyanate-based crosslinking agent).
[0033] The type of the monomer having an amino group is not particularly limited. Specific examples of monomers having a primary amino group include acrylamide and methacrylamide. Specific examples of the monomer having a secondary amino group include N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, and N-methoxyethyl(meth)acrylamide.
[0034] The specific (meth)acrylic polymer (A) may contain only one type of structural unit derived from a monomer having a crosslinkable functional group, or may contain two or more types.
[0035] The content of the structural units derived from the monomer having a crosslinkable functional group in the specific (meth)acrylic polymer (A) is not particularly limited, but for example, relative to all structural units of the specific (meth)acrylic polymer (A), is preferably 1 mass% to 40 mass%, more preferably 1 mass% to 35 mass%, even more preferably 2 mass% to 30 mass%, even more preferably 2 mass% to 25 mass%, and particularly preferably 3 mass% to 20 mass%. When the content of the structural units derived from the monomer having a crosslinkable functional group in the specific (meth)acrylic polymer (A) is within the above range relative to all structural units of the specific (meth)acrylic polymer (A), there is a tendency that a pressure-sensitive adhesive layer can be formed in which the easy peelability at the initial stage of bonding is less likely to be impaired over time.
[0036] <Structural Unit Derived from (Meth)acrylic Acid Alkyl Ester Monomer> The specific (meth)acrylic polymer (A) preferably contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer. The structural units derived from the (meth)acrylic acid alkyl ester monomer can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.
[0037] In the present disclosure, the term "structural unit derived from a (meth)acrylic acid alkyl ester monomer" refers to a structural unit formed by addition polymerization of a (meth)acrylic acid alkyl ester monomer.
[0038] The type of the (meth)acrylic acid alkyl ester monomer is not particularly limited. Note that the "(meth)acrylic acid alkyl ester monomer" in the specific (meth)acrylic polymer (A) does not include a monomer that corresponds to a monomer having a crosslinkable functional group. The (meth)acrylic acid alkyl ester monomer is preferably an unsubstituted (meth)acrylic acid alkyl ester monomer. The alkyl group of the (meth)acrylic acid alkyl ester monomer may be linear, branched, or cyclic. The alkyl group preferably has 1 to 18 carbon atoms, and more preferably has 1 to 12 carbon atoms, for example.
[0039] Specific examples of the (meth)acrylic acid alkyl ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-octyl (meth)acrylate, i-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-nonyl (meth)acrylate, i-nonyl (meth)acrylate, n-decyl (meth)acrylate, stearyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate. As the (meth)acrylic acid alkyl ester monomer, for example, from the viewpoint of easiness in producing a (meth)acrylic copolymer having a glass transition temperature of less than 0°C, at least one selected from the group consisting of n-butyl acrylate (n-BA), methyl acrylate (MA), and 2-ethylhexyl acrylate (2EHA) is preferred.
[0040] When the specific (meth)acrylic polymer (A) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, it may contain only one type of structural unit derived from the (meth)acrylic acid alkyl ester monomer, or it may contain two or more types of structural units derived from the (meth)acrylic acid alkyl ester monomer.
[0041] When the specific (meth)acrylic polymer (A) contains a structural unit derived from a (meth)acrylic acid alkyl ester monomer, the content of the structural unit derived from the (meth)acrylic acid alkyl ester monomer in the specific (meth)acrylic polymer (A) is not particularly limited, but for example, relative to all structural units of the specific (meth)acrylic polymer (A), is preferably 50 mass% or more, more preferably 50 mass% to 99 mass%, even more preferably 60 mass% to 99 mass%, even more preferably 65 mass% to 99 mass%, even more preferably 70 mass% to 98 mass%, even more preferably 75 mass% to 98 mass%, and particularly preferably 80 mass% to 97 mass%. Here, the content of the structural units derived from the (meth)acrylic acid alkyl ester monomer being 50 mass% or more relative to the total structural units of the specific (meth)acrylic polymer (A) means that the structural units derived from the (meth)acrylic acid alkyl ester monomer are contained as the main component of the structural units constituting the specific (meth)acrylic polymer (A).
[0042] <Other building blocks> The specific (meth)acrylic polymer (A) may contain structural units (so-called other structural units) other than the above-described structural units, i.e., the structural unit derived from a monomer having a crosslinkable functional group, which is an essential structural unit, and the structural unit derived from a (meth)acrylic acid alkyl ester monomer, which is an optional structural unit, within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0043] Examples of monomers constituting other structural units include aromatic ring-containing (meth)acrylates such as benzyl (meth)acrylate and phenoxyethyl (meth)acrylate, alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.
[0044] When the specific (meth)acrylic polymer (A) contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.
[0045] When the specific (meth)acrylic polymer (A) contains other structural units, the content of the other structural units in the specific (meth)acrylic polymer (A) is not particularly limited and can be appropriately set depending on the purpose as long as the effects of the pressure-sensitive adhesive composition of the present disclosure are not impaired.
[0046] <<Glass transition temperature of specific (meth)acrylic polymer (A)>> The glass transition temperature (hereinafter also referred to as "Tg") of the specific (meth)acrylic polymer (A) is less than 0°C, preferably -10°C or lower, more preferably -20°C or lower, even more preferably -30°C or lower, and particularly preferably -40°C or lower. When the glass transition temperature of the specific (meth)acrylic polymer (A) is less than 0° C., it tends to be possible to form a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating. Also, when the glass transition temperature of the specific (meth)acrylic polymer (A) is less than 0° C., it tends to be possible to form a pressure-sensitive adhesive layer that has good compatibility with the adherend. The reason for the above tendency is thought to be that the pressure-sensitive adhesive layer formed is given appropriate wettability. The lower limit of the glass transition temperature of the specific (meth)acrylic polymer (A) is not particularly limited, but is preferably, for example, −70° C. or higher.
[0047] The glass transition temperature of the specific (meth)acrylic polymer (A) is a value obtained by converting the absolute temperature (unit: K; the same applies below) calculated from the following formula 1 into Celsius temperature (unit: °C; the same applies below). 1 / Tg=m1 / Tg1+m2 / Tg2+ +m(k-1) / Tg(k-1)+mk / Tgk (Formula 1)
[0048] In formula 1, Tg1, Tg2, . . . , Tg(k-1), and Tgk respectively represent the glass transition temperatures expressed as absolute temperatures when each monomer constituting the specific (meth)acrylic polymer (A) is made into a homopolymer. m1, m2, . . . , m(k-1), and mk respectively represent the molar fractions of each monomer constituting the specific (meth)acrylic polymer (A), and m1 + m2 + . . . + m(k-1) + mk = 1. Note that absolute temperatures can be converted to Celsius temperatures by subtracting 273 from the absolute temperature, and Celsius temperatures can be converted to absolute temperatures by adding 273 to the Celsius temperature.
[0049] In the present disclosure, the "glass transition temperature expressed as absolute temperature when made into a homopolymer" refers to the glass transition temperature expressed as absolute temperature of a homopolymer produced by polymerizing the monomer alone. The glass transition temperature of the homopolymer was measured using a differential scanning calorimeter (DSC) [model: EXSTAR6000, manufactured by Seiko Instruments Inc.] under conditions of a nitrogen gas flow, a measurement sample of 10 mg, and a heating rate of 10°C / min, and the inflection point of the obtained DSC curve was taken as the glass transition temperature of the homopolymer.
[0050] The glass transition temperatures of representative monomers, expressed in Celsius degrees when made into homopolymers, are: 2-ethylhexyl acrylate (2EHA) -76°C, 2-ethylhexyl methacrylate (2EHMA) -10°C, n-butyl acrylate (n-BA) -57°C, n-butyl methacrylate (n-BMA) 21°C, t-butyl acrylate (t-BA) 41°C, t-butyl methacrylate (t-BMA) 107°C, i-butyl methacrylate (i-BMA) 48°C, methyl acrylate (MA) 5°C, methyl methacrylate (MMA) 103°C, isobornyl methacrylate (IBXMA) 155°C, isobornyl acrylate (IBXA) 96°C, and ethyl acrylate ( EA) at -27°C, methacrylic acid (MAA) at 185°C, 4-hydroxybutyl acrylate (4HBA) at -39°C, 2-hydroxyethyl acrylate (2HEA) at -15°C, 2-hydroxyethyl methacrylate (2HEMA) at 55°C, 2-hydroxypropyl acrylate (2HPA) at -7°C, acrylic acid (AA) at 163°C, n-octyl acrylate (n-OA) at -65°C, i-octyl acrylate (i-OA) at -75°C, i-decyl acrylate at -62°C, dimethylaminoethyl methacrylate (DM) at 18°C, ω-carboxy-polycaprolactone (n≒2) monoacrylate at -30°C, and 2-acryloyloxyethyl-succinic acid at -40°C.
[0051] The glass transition temperature of the specific (meth)acrylic polymer (A) can be appropriately adjusted, for example, by using two or more kinds of monomers having different glass transition temperatures when formed into homopolymers.
[0052] <<Weight average molecular weight of specific (meth)acrylic polymer (A)>> The weight average molecular weight (hereinafter also referred to as "Mw") of the specific (meth)acrylic polymer (A) is not particularly limited, but is, for example, preferably 400,000 to 2,000,000, more preferably 400,000 to 1,500,000, even more preferably 400,000 to 1,000,000, and particularly preferably 400,000 to 800,000. When the weight average molecular weight of the specific (meth)acrylic polymer (A) is 400,000 or more, a pressure-sensitive adhesive layer that exhibits better easy peelability at the initial stage of lamination tends to be formed. When the weight average molecular weight of the specific (meth)acrylic polymer (A) is 2,000,000 or less, there is a tendency that a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating can be formed.
[0053] The weight average molecular weight of the specific (meth)acrylic polymer (A) is a value measured by the following method, specifically, according to the following (1) to (3). (1) A solution of the specific (meth)acrylic polymer (A) is applied to a release paper and dried at 100° C. for 1 minute to obtain a film of the specific (meth)acrylic polymer (A). (2) Using the film-like specific (meth)acrylic polymer (A) obtained in (1) above and tetrahydrofuran, a sample solution having a solid content concentration of 0.2% by mass is obtained. Note that the "solid content concentration" here means the mass ratio of the specific (meth)acrylic polymer (A) in the sample solution. (3) The weight average molecular weight of the specific (meth)acrylic polymer (A) is measured in terms of standard polystyrene using gel permeation chromatography (GPC) under the following conditions.
[0054] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min
[0055] The weight average molecular weight of the specific (meth)acrylic polymer (A) can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, and the like.
[0056] <<Content of specific (meth)acrylic polymer (A)>> The content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 75 mass% to 99.85 mass%, more preferably 80 mass% to 99.8 mass%, even more preferably 80 mass% to 99 mass%, and particularly preferably 80 mass% to 98 mass%, relative to the total solid content in the pressure-sensitive adhesive composition. When the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 75% by mass or more based on the total solid content in the pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that exhibits higher adhesive strength after heating tends to be formed. Also, when the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 75% by mass or more based on the total solid content in the pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that exhibits better compatibility with the adherend tends to be formed. When the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 99.85 mass% or less based on the total solid content in the pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that exhibits better easy peelability at the beginning of lamination tends to be formed. Also, when the content of the specific (meth)acrylic polymer (A) in the pressure-sensitive adhesive composition of the present disclosure is 99.85 mass% or less based on the total solid content in the pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer that is less likely to lose its easy peelability over time at the beginning of lamination tends to be formed. In the present disclosure, the "total solid content in the PSA composition" means the total mass of the PSA composition when the PSA composition does not contain a solvent, and means the mass of the residue remaining after removing the solvent from the PSA composition when the PSA composition contains a solvent. In this disclosure, "solvent" means water and organic solvents.
[0057] [Specific (meth)acrylic copolymer (B)] The pressure-sensitive adhesive composition of the present disclosure contains a (meth)acrylic copolymer (B) [i.e., specific (meth)acrylic copolymer (B)] which contains 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, relative to all structural units, and 25% by mass to 45% by mass of structural units derived from a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or higher and lower than 10°C when made into a homopolymer, and has a weight average molecular weight of 40,000 to 400,000. The number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000, and the content of the specific (meth)acrylic copolymer (B) is 0.1 to 21 parts by mass per 100 parts by mass of the above-mentioned specific (meth)acrylic polymer (A).
[0058] <Structural Units Derived from Monomers Having an Organosiloxane Skeleton> The specific (meth)acrylic copolymer (B) contains 0.1% by mass to 10% by mass of a structural unit derived from a monomer having an organosiloxane skeleton (hereinafter also referred to as "structural unit B1") relative to all structural units, and the number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000. In the present disclosure, a "structural unit derived from a monomer having an organosiloxane skeleton (i.e., structural unit B1)" refers to a structural unit formed by addition polymerization of a monomer having an organosiloxane skeleton.
[0059] The number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000, preferably in the range of 4,200 or more and less than 20,000, more preferably in the range of 4,500 or more and less than 20,000, and even more preferably in the range of 5,000 or more and less than 15,000. The number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is, for example, less than 20,000 from the viewpoint of easy availability of the monomer having an organosiloxane skeleton. When the number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is 4000 or more, it tends to be possible to form a pressure-sensitive adhesive layer in which the easy peelability at the initial stage of bonding is unlikely to be impaired over time. The reason for this tendency is thought to be that the polarity of the specific (meth)acrylic copolymer (B) is sufficiently low, and the uneven distribution of the (meth)acrylic copolymer (B) on the adhesive surface of the pressure-sensitive adhesive layer is sufficiently maintained.
[0060] In the present disclosure, the number average molecular weight of a monomer having an organosiloxane skeleton is a value measured by the following method. Specifically, it is measured according to the following (1) and (2). (1) A sample solution having a solid content of 0.2% by mass is prepared using a monomer having an organosiloxane skeleton and tetrahydrofuran. Note that the "solid content concentration" here refers to the mass ratio of the monomer having an organosiloxane skeleton in the sample solution. (2) Using gel permeation chromatography (GPC), measure the number average molecular weight of the monomer having an organosiloxane skeleton in terms of standard polystyrene under the following conditions.
[0061] ~Conditions~ Measurement equipment: High-speed GPC [Model: HLC-8220 GPC, manufactured by Tosoh Corporation] Detector: Differential refractometer (RI) [installed in HLC-8220, manufactured by Tosoh Corporation] Column: TSKgel GMH XL Four Tosoh Corporation-made Column temperature: 40℃ Eluent: Tetrahydrofuran Sample solution injection volume: 100μL Flow rate: 0.8mL / min
[0062] In addition, when the specific (meth)acrylic copolymer (B) contains two or more types of monomers having an organosiloxane skeleton with different number average molecular weights, the "number average molecular weight of the monomers having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B)" means an arithmetic average value, specifically, a value calculated by the following formula. Number average molecular weight of monomer having organosiloxane skeleton in specific (meth)acrylic copolymer (B) = [number average molecular weight of monomer 1 × amount of monomer 1 + number average molecular weight of monomer 2 × amount of monomer 2 + ··· + number average molecular weight of monomer n × amount of monomer n] / [amount of monomer 1 + amount of monomer 2 + ··· + amount of monomer n]
[0063] The type of monomer having an organosiloxane skeleton is not particularly limited, so long as the number average molecular weight of the monomer having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000. A specific example of the monomer having an organosiloxane skeleton is a compound represented by the following formula (1).
[0064] [ka]
[0065] In formula (1), R 1 represents a hydrogen atom or a methyl group, and is preferably a methyl group.
[0066] In formula (1), R 2 represents a monovalent organic group. R 2 The monovalent organic group represented by the following formula (1) may be linear, branched, or cyclic. Examples of the monovalent organic group include an alkyl group, an alkenyl group, an alkynyl group, and an aryl group, and an alkyl group is preferred. R 2When represents an alkyl group, the alkyl group is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 6 carbon atoms, and further preferably an alkyl group having 1 to 4 carbon atoms. Examples of the alkyl group having 1 to 4 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, and a t-butyl group, with a methyl group being preferred. R 2 When represents an alkenyl group, examples of the alkenyl group include a vinyl group, an allyl group, and a 2-propenyl group, and a vinyl group is preferred. R 2 When represents an alkynyl group, examples of the alkynyl group include an ethynyl group, a propargyl group, and a prop-2-yn-1-yl group, and an ethynyl group is preferable. R 2 When represents an aryl group, examples of the aryl group include a phenyl group, a tolyl group, and a pyridyl group, and a phenyl group is preferable.
[0067] In formula (1), m and n each independently represent 0 or an integer of 1 or more, but m and n cannot simultaneously represent 0. m is preferably an integer from 1 to 10, and more preferably an integer from 1 to 6. n is preferably an integer from 1 to 250, and more preferably an integer from 5 to 200, and even more preferably an integer from 10 to 200.
[0068] As the monomer having an organosiloxane skeleton, a commercially available product can be used. Examples of commercially available products of monomers having an organosiloxane skeleton include X-22-2404 (trade name, number average molecular weight: 420, manufactured by Shin-Etsu Chemical Co., Ltd.), X-22-174ASX (trade name, number average molecular weight: 1100, manufactured by Shin-Etsu Chemical Co., Ltd.), Silaplane (registered trademark) FM-0711 (trade name, number average molecular weight: 1200, manufactured by JNC Corporation), Silaplane (registered trademark) FM-0721 (trade name, number average molecular weight: 6500, manufactured by JNC Corporation), Silaplane (registered trademark) FM-0725 (trade name, number average molecular weight: 15000, manufactured by JNC Corporation), KF-2012 (trade name, number average molecular weight: 5400, manufactured by Shin-Etsu Chemical Co., Ltd.), and X-22-2426 (trade name, number average molecular weight: 13800, manufactured by Shin-Etsu Chemical Co., Ltd.). All of the above commercially available products correspond to the compound represented by formula (1).
[0069] The specific (meth)acrylic copolymer (B) may contain only one type of the structural unit B1, or may contain two or more types.
[0070] The content of the structural unit B1 in the specific (meth)acrylic copolymer (B) is 0.1% by mass to 10% by mass based on all structural units of the specific (meth)acrylic copolymer (B). The content of the structural unit B1 in the specific (meth)acrylic copolymer (B) being 0.1 mass% or more relative to the total structural units of the specific (meth)acrylic copolymer (B) means that the specific (meth)acrylic copolymer (B) actively contains the structural unit B1. The content of the structural unit B1 in the specific (meth)acrylic copolymer (B) is, for example, preferably 0.5 mass% or more, more preferably 1 mass% or more, even more preferably 2 mass% or more, and particularly preferably 3 mass% or more, based on all structural units of the specific (meth)acrylic copolymer (B). When the content of the structural unit B1 in the specific (meth)acrylic copolymer (B) is 10 mass% or less relative to all structural units of the specific (meth)acrylic copolymer (B), there is a tendency that a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating can be formed. From this viewpoint, the content of the structural unit B1 in the specific (meth)acrylic copolymer (B) is 10 mass% or less, preferably 9 mass% or less, more preferably 8 mass% or less, and even more preferably 7 mass% or less, based on the total structural units of the specific (meth)acrylic copolymer (B).
[0071] <Structural unit derived from a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or more and less than 10°C when made into a homopolymer> The specific (meth)acrylic copolymer (B) contains 25% by mass to 45% by mass of structural units derived from a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or more and less than 10°C when made into a homopolymer (hereinafter also referred to as "structural unit B2"), relative to all structural units. In the present disclosure, "a structural unit derived from a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or more and less than 10°C when made into a homopolymer (i.e., structural unit B2)" means a structural unit formed by addition polymerization of a (meth)acrylic monomer having a glass transition temperature in the range of -30°C or more and less than 10°C when made into a homopolymer.
[0072] The (meth)acrylic monomer having a glass transition temperature in the range of −30° C. or more and less than 10° C. when made into a homopolymer is not particularly limited, but is preferably a (meth)acrylic acid alkyl ester monomer, more preferably a (meth)acrylic acid alkyl ester monomer having no crosslinkable functional group, and further preferably an unsubstituted (meth)acrylic acid alkyl ester monomer.
[0073] Specific examples of (meth)acrylic monomers having a glass transition temperature in the range of −30° C. or more and less than 10° C. when made into a homopolymer include methyl acrylate (MA, glass transition temperature when made into a homopolymer: 5° C.), 2-ethylhexyl methacrylate (2EHMA, glass transition temperature when made into a homopolymer: −10° C.), ethyl acrylate (EA, glass transition temperature when made into a homopolymer: −27° C.), 2-hydroxyethyl acrylate (2HEA, glass transition temperature when made into a homopolymer: −15° C.), 2-hydroxypropyl acrylate (2HPA, glass transition temperature when made into a homopolymer: −7° C.), and ω-carboxy-polycaprolactone (n≒2) monoacrylate (glass transition temperature when made into a homopolymer: −30° C.).
[0074] The specific (meth)acrylic copolymer (B) may contain only one type of the structural unit B2, or may contain two or more types.
[0075] The content of the structural unit B2 in the specific (meth)acrylic copolymer (B) is 25% by mass to 45% by mass, preferably 25% by mass to 43% by mass, more preferably 25% by mass to 40% by mass, and even more preferably 25% by mass to 35% by mass, based on all structural units of the specific (meth)acrylic copolymer (B). When the content of the structural unit B2 in the specific (meth)acrylic copolymer (B) is 25 mass% or more relative to all structural units of the specific (meth)acrylic copolymer (B), a pressure-sensitive adhesive layer having good compatibility with the adherend tends to be formed. When the content of the structural unit B2 in the specific (meth)acrylic copolymer (B) is 45 mass% or less relative to all structural units of the specific (meth)acrylic copolymer (B), it tends to be possible to form a pressure-sensitive adhesive layer whose easy peelability at the initial stage of bonding is not easily impaired over time.
[0076] <Structural unit derived from a (meth)acrylic polymer having a glass transition temperature of less than -30°C or 10°C or higher when formed into a homopolymer> The specific (meth)acrylic copolymer (B) can contain, in addition to the structural unit B1 and the structural unit B2, a structural unit derived from a (meth)acrylic polymer having a glass transition temperature of less than −30° C. or 10° C. or higher when made into a homopolymer (hereinafter also referred to as “structural unit B3”). The structural unit B3 can contribute to adjusting the adhesive strength of the pressure-sensitive adhesive layer.
[0077] In the present disclosure, "a structural unit derived from a (meth)acrylic polymer having a glass transition temperature of less than -30°C or 10°C or higher when made into a homopolymer (i.e., structural unit B3)" means a structural unit formed by addition polymerization of a (meth)acrylic polymer having a glass transition temperature of less than -30°C or 10°C or higher when made into a homopolymer.
[0078] The (meth)acrylic monomer having a glass transition temperature of less than −30° C. or not less than 10° C. when made into a homopolymer is not particularly limited, but is preferably a (meth)acrylic acid alkyl ester monomer, more preferably a (meth)acrylic acid alkyl ester monomer having no crosslinkable functional group, and further preferably an unsubstituted (meth)acrylic acid alkyl ester monomer.
[0079] Specific examples of (meth)acrylic monomers having a glass transition temperature of less than -30°C or 10°C or higher when made into a homopolymer include n-butyl acrylate (n-BA, glass transition temperature when made into a homopolymer: -57°C), n-butyl methacrylate (n-BMA, glass transition temperature when made into a homopolymer: 21°C), methyl methacrylate (MMA, glass transition temperature when made into a homopolymer: 103°C), 2-ethylhexyl acrylate (2EHA, glass transition temperature when made into a homopolymer: 103°C), and 2-ethylhexyl acrylate (2EHA, glass transition temperature when made into a homopolymer: 103°C). Glass transition temperature when homopolymerized: -76°C), t-butyl acrylate (t-BA, glass transition temperature when homopolymerized: 41°C), t-butyl methacrylate (t-BMA, glass transition temperature when homopolymerized: 107°C), i-butyl methacrylate (i-BMA, glass transition temperature when homopolymerized: 48°C), isobornyl methacrylate (IBXMA, glass transition temperature when homopolymerized: 155°C), isobornyl acrylate (IBXMA, glass transition temperature when homopolymerized: 155°C), XA, glass transition temperature when homopolymerized: 96°C), methacrylic acid (MAA, glass transition temperature when homopolymerized: 185°C), 4-hydroxybutyl acrylate (4HBA, glass transition temperature when homopolymerized: -39°C), 2-hydroxyethyl methacrylate (2HEMA, glass transition temperature when homopolymerized: 55°C), acrylic acid (AA, glass transition temperature when homopolymerized: 163°C), n-octyl acrylate (n Examples of the acrylate copolymers include i-O-A, glass transition temperature when homopolymerized: -65°C), i-octyl acrylate (i-O-A, glass transition temperature when homopolymerized: -75°C), i-decyl acrylate (glass transition temperature when homopolymerized: -62°C), dimethylaminoethyl methacrylate (DM, glass transition temperature when homopolymerized: 18°C), and 2-acryloyloxyethyl-succinic acid (glass transition temperature when homopolymerized: -40°C).
[0080] When the specific (meth)acrylic copolymer (B) contains the structural unit B3, it may contain only one type of the structural unit B3, or may contain two or more types of the structural unit B3.
[0081] When the specific (meth)acrylic copolymer (B) contains the structural unit B3, the content of the structural unit B3 in the specific (meth)acrylic copolymer (B) is not particularly limited, but for example, it is preferably 45% by mass to 74.5% by mass, more preferably 46% by mass to 74% by mass, even more preferably 47% by mass to 73% by mass, and particularly preferably 48% by mass to 72% by mass, relative to all structural units of the specific (meth)acrylic copolymer (B).
[0082] <Other building blocks> The specific (meth)acrylic copolymer (B) may contain structural units other than the above-described structural units, i.e., the structural units B1 and B2, which are essential structural units, and the structural unit B3, which is an optional structural unit (so-called other structural units), within the scope of not impairing the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0083] Examples of monomers constituting the other structural units include aromatic monovinyls such as styrene, α-methylstyrene, t-butylstyrene, p-chlorostyrene, chloromethylstyrene, and vinyltoluene, vinyl cyanides such as acrylonitrile and methacrylonitrile, and vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, and vinyl versatate. Also included are various derivatives of these monomers.
[0084] When the specific (meth)acrylic copolymer (B) contains other structural units, it may contain only one type of other structural unit, or may contain two or more types of other structural units.
[0085] When the specific (meth)acrylic copolymer (B) contains other structural units, the content of the other structural units in the specific (meth)acrylic copolymer (B) is not particularly limited and can be appropriately set depending on the purpose as long as the effect of the pressure-sensitive adhesive composition of the present disclosure is not impaired.
[0086] <<Glass transition temperature of specific (meth)acrylic copolymer (B)>> The glass transition temperature of the specific (meth)acrylic copolymer (B) is not particularly limited, but is, for example, preferably from 20°C to 50°C, more preferably from 20°C to 45°C, and even more preferably from 20°C to 40°C.
[0087] The glass transition temperature of the specific (meth)acrylic copolymer (B) was measured using a differential scanning calorimeter (DSC) in a nitrogen gas flow using 8 mg of a measurement sample under conditions of a measurement start temperature of -70°C, a measurement end temperature of 150°C, and a heating rate of 10°C / min, and the inflection point of the obtained DSC curve was taken as the glass transition temperature of the specific (meth)acrylic copolymer (B). As a differential scanning calorimeter, for example, DSC2500 (model number) manufactured by TA Instruments Co., Ltd. can be suitably used. However, the differential scanning calorimeter is not limited to this.
[0088] The glass transition temperature of the specific (meth)acrylic copolymer (B) can be appropriately adjusted, for example, by using two or more kinds of monomers having different glass transition temperatures when formed into homopolymers.
[0089] <<Weight average molecular weight of specific (meth)acrylic copolymer (B)>> The weight average molecular weight of the specific (meth)acrylic copolymer (B) is 40,000 to 400,000. When the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 40,000 or more, a pressure-sensitive adhesive layer having good compatibility with an adherend tends to be formed. From this viewpoint, the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 40,000 or more, preferably 50,000 or more, more preferably 60,000 or more, even more preferably 70,000 or more, and particularly preferably 80,000 or more. When the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 400,000 or less, a pressure-sensitive adhesive layer that exhibits easy peelability at the initial stage of lamination tends to be formed. Also, when the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 400,000 or less, a pressure-sensitive adhesive layer that is unlikely to lose its easy peelability at the initial stage of lamination over time tends to be formed. From this viewpoint, the weight average molecular weight of the specific (meth)acrylic copolymer (B) is 400,000 or less, preferably 350,000 or less, more preferably 300,000 or less, even more preferably 250,000 or less, and particularly preferably 200,000 or less.
[0090] The weight average molecular weight of the specific (meth)acrylic copolymer (B) is measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.
[0091] The weight average molecular weight of the specific (meth)acrylic copolymer (B) can be adjusted to a desired value by adjusting the polymerization temperature, polymerization time, amount of organic solvent used, type of polymerization initiator, amount of polymerization initiator used, and the like.
[0092] <<Content of specific (meth)acrylic copolymer (B)>> The content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is 0.1 to 21 parts by mass relative to 100 parts by mass of the specific (meth)acrylic polymer (A). The content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure being 0.1 part by mass or more per 100 parts by mass of the specific (meth)acrylic polymer (A) means that the pressure-sensitive adhesive composition of the present disclosure actively contains the specific (meth)acrylic copolymer (B). The content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is, for example, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3% by mass or more, and particularly preferably 5% by mass or more, relative to 100 parts by mass of the specific (meth)acrylic polymer (A). When the content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is 21 parts by mass or less per 100 parts by mass of the specific (meth)acrylic polymer (A), a pressure-sensitive adhesive layer that exhibits high adhesive strength after heating tends to be formed. From such a viewpoint, the content of the specific (meth)acrylic copolymer (B) in the pressure-sensitive adhesive composition of the present disclosure is 21 parts by mass or less, preferably 18 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 12 parts by mass or less, relative to 100 parts by mass of the specific (meth)acrylic polymer (A).
[0093] [Method for producing specific (meth)acrylic polymer] The method for producing the specific (meth)acrylic polymer (A) and the specific (meth)acrylic copolymer (B) [i.e., the specific (meth)acrylic polymer] is not particularly limited. The specific (meth)acrylic polymer can be produced by polymerizing the above-mentioned monomers by a known polymerization method typified by, for example, a solution polymerization method, an emulsion polymerization method, a suspension polymerization method, or a bulk polymerization method. As a polymerization method, a solution polymerization method is preferred in that the processing steps are relatively simple and can be carried out in a short time when preparing the pressure-sensitive adhesive composition of the present disclosure after production.
[0094] In the solution polymerization method, a predetermined organic solvent, a monomer, a polymerization initiator, and a chain transfer agent used as required are generally charged into a polymerization tank, and the mixture is heated and reacted for several hours with stirring at the reflux temperature of the organic solvent in a nitrogen stream. In this case, at least a portion of the organic solvent, the monomer, the polymerization initiator, and the chain transfer agent used as required may be added successively.
[0095] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, alicyclic hydrocarbon compounds, ester compounds, ketone compounds, glycol ether compounds, and alcohol compounds. More specifically, examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbon compounds such as benzene, toluene, ethylbenzene, n-propylbenzene, t-butylbenzene, o-xylene, m-xylene, p-xylene, tetralin, decalin, and aromatic naphtha; aliphatic or alicyclic hydrocarbon compounds such as n-hexane, n-heptane, n-octane, i-octane, n-decane, dipentene, petroleum spirit, petroleum naphtha, and turpentine oil; ester compounds such as ethyl acetate, n-butyl acetate, n-amyl acetate, 2-hydroxyethyl acetate, 2-butoxyethyl acetate, 3-methoxybutyl acetate, and methyl benzoate; acetone, methyl ethyl acetate, and the like. Examples of the alcohol compounds include ketones, ketone compounds represented by methyl-i-butyl ketone, isophorone, cyclohexanone, and methylcyclohexanone, glycol ether compounds represented by ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, and diethylene glycol monobutyl ether, and alcohol compounds represented by methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, s-butyl alcohol, and t-butyl alcohol.
[0096] In producing the specific (meth)acrylic polymer, it is preferable to use an organic solvent that is unlikely to cause chain transfer during the polymerization reaction, such as an aromatic hydrocarbon compound, an ester compound, or a ketone compound. In particular, it is preferable to use ethyl acetate from the viewpoints of the solubility of the specific (meth)acrylic polymer, ease of polymerization reaction, and the like.
[0097] During the polymerization reaction, only one type of organic solvent may be used, or two or more types may be used.
[0098] Examples of the polymerization initiator include organic peroxides and azo compounds that are used in ordinary solution polymerization methods. Specific examples of organic peroxides include t-butyl hydroperoxide, cumene hydroperoxide, dicumyl peroxide, benzoyl peroxide, lauroyl peroxide, caproyl peroxide, di-i-propyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, t-butyl peroxypivalate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-amylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-octylperoxycyclohexyl)propane, 2,2-bis(4,4-di-α-cumylperoxycyclohexyl)propane, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)butane, and 2,2-bis(4,4-di-t-octylperoxycyclohexyl)butane. Specific examples of azo compounds include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ABVN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis(isobutyrate) dimethyl. In producing the specific (meth)acrylic polymer, it is preferable to use a polymerization initiator that does not cause a graft reaction during the polymerization reaction, and it is particularly preferable to use an azo compound.
[0099] In the polymerization reaction, only one type of polymerization initiator may be used, or two or more types may be used.
[0100] The amount of the polymerization initiator used is not particularly limited, and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.
[0101] In producing the specific (meth)acrylic polymer, a chain transfer agent may be used, if necessary. Examples of the chain transfer agent include cyanoacetic acid, alkyl ester compounds of cyanoacetic acid having 1 to 8 carbon atoms, bromoacetic acid, alkyl ester compounds of bromoacetic acid having 1 to 8 carbon atoms, aromatic compounds such as α-methylstyrene, anthracene, phenanthrene, fluorene, and 9-phenylfluorene, aromatic nitro compounds such as p-nitroaniline, nitrobenzene, dinitrobenzene, p-nitrobenzoic acid, p-nitrophenol, and p-nitrotoluene, benzoquinone derivatives such as benzoquinone and 2,3,5,6-tetramethyl-p-benzoquinone, borane derivatives such as tributylborane, carbon tetrabromide, ... Examples of the halogenated hydrocarbon compounds include carbon chloride, 1,1,2,2-tetrabromoethane, tribromoethylene, trichloroethylene, bromotrichloromethane, tribromomethane, and 3-chloro-1-propene, aldehyde compounds such as chloral and furaldehyde, alkyl mercaptan compounds having 1 to 18 carbon atoms, aromatic mercaptan compounds such as thiophenol and toluene mercaptan, mercaptoacetic acid, alkyl ester compounds of mercaptoacetic acid having 1 to 10 carbon atoms, hydroxyalkyl mercaptan compounds having 1 to 12 carbon atoms, and terpene compounds such as pinene and terpinolene.
[0102] When a chain transfer agent is used in producing the specific (meth)acrylic polymer, the amount of the chain transfer agent used is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.
[0103] The polymerization temperature is not particularly limited and can be appropriately set depending on, for example, the molecular weight of the target specific (meth)acrylic polymer.
[0104] [Crosslinking Agent] The pressure-sensitive adhesive composition of the present disclosure contains a crosslinking agent. The type of crosslinking agent is not particularly limited. Examples of the crosslinking agent include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and a metal chelate-based crosslinking agent. Among these, the crosslinking agent is preferably an isocyanate-based crosslinking agent or a metal chelate-based crosslinking agent, and more preferably an isocyanate-based crosslinking agent.
[0105] In this disclosure, the term "isocyanate-based crosslinking agent" refers to a compound having two or more isocyanate groups in one molecule (so-called polyisocyanate compound). The term "epoxy-based crosslinking agent" refers to a compound having two or more epoxy groups in one molecule (so-called bifunctional or higher epoxy compound). The term "metal chelate-based crosslinking agent" refers to a metal chelate compound that functions as a crosslinking agent.
[0106] The type of the isocyanate-based crosslinking agent is not particularly limited. Examples of the isocyanate crosslinking agent include aromatic polyisocyanate compounds such as xylylene diisocyanate (XDI), diphenylmethane diisocyanate, triphenylmethane triisocyanate, and tolylene diisocyanate (TDI), and aliphatic polyisocyanate compounds or alicyclic polyisocyanate compounds such as hexamethylene diisocyanate (HMDI), pentamethylene diisocyanate (PDI), isophorone diisocyanate, and hydrogenated aromatic polyisocyanate compounds. Further, examples of the isocyanate-based crosslinking agent include dimers, trimers, and pentamers of the above polyisocyanate compounds, adducts of the above polyisocyanate compounds with polyol compounds such as trimethylolpropane, and biuret forms of the above polyisocyanate compounds.
[0107] As the isocyanate-based crosslinking agent, a commercially available product can be used. Examples of commercially available isocyanate crosslinking agents include "Coronate (registered trademark) HX", "Coronate (registered trademark) HL-S", "Coronate (registered trademark) L", "Coronate (registered trademark) L-45E", "Coronate (registered trademark) 2031", "Coronate (registered trademark) 2037", "Coronate (registered trademark) 2234", "Coronate (registered trademark) 2785", "Aquanate (registered trademark) 200", and "Aquanate (registered trademark) 210" (all manufactured by Tosoh Corporation), "Sumidur (registered trademark) N3300", "Desmodur (registered trademark) N3400", and "Sumidur (registered trademark) N75" (all manufactured by Sumika Covestro Urethane Co., Ltd.), "Duranate (registered trademark) E-405-80T", "Duranate (registered trademark) AE700-100", "Duranate (registered trademark) Examples of such polyurethane foams include "Duranate (registered trademark) 24A-100" and "Duranate (registered trademark) TSE-100" (all manufactured by Asahi Kasei Corporation), as well as "Takenate (registered trademark) D-110N", "Takenate (registered trademark) D-120N", "Takenate (registered trademark) M-631N", "MT-Olestar (registered trademark) NP1200", and "STABIO (registered trademark) XD-340N" (all manufactured by Mitsui Chemicals, Inc.).
[0108] The type of the epoxy crosslinking agent is not particularly limited. Specific examples of epoxy crosslinking agents include ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, polyglycerol di ... Examples of such glycidyl ethers include glycerol polyglycidyl ether, resorcinol diglycidyl ether, 2,2-dibromoneopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol polyglycidyl ether, sorbitol polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, tris(glycidyl)isocyanurate, tris(glycidoxyethyl)isocyanurate, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-1,3-benzenedi(methanamine).
[0109] As the epoxy-based crosslinking agent, a commercially available product can be used. Examples of commercially available epoxy crosslinking agents include "TETRAD (registered trademark)-X" and "TETRAD (registered trademark)-C" (both manufactured by Mitsubishi Gas Chemical Company, Inc.).
[0110] The type of the metal chelate crosslinking agent is not particularly limited. Examples of metal chelate crosslinking agents include aluminum chelate compounds such as aluminum monoacetylacetonate bis(ethylacetoacetate), aluminum tris(ethylacetoacetate), and aluminum tris(acetylacetonate), titanium chelate compounds, zirconium chelate compounds, and cobalt chelate compounds.
[0111] As the metal chelate crosslinking agent, commercially available products can be used. Examples of commercially available metal chelate crosslinking agents include Aluminum Chelate A (trade name: aluminum tris(acetylacetonate), manufactured by Kawaken Fine Chemicals Co., Ltd.), Aluminum Chelate D (trade name: aluminum monoacetylacetonate bis(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.), and ALCH-TR (trade name: aluminum tris(ethylacetoacetate), manufactured by Kawaken Fine Chemicals Co., Ltd.).
[0112] The pressure-sensitive adhesive composition of the present disclosure may contain only one type of crosslinking agent, or may contain two or more types.
[0113] The content of the crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is not particularly limited, but for example, it is preferably 0.05 parts by mass to 10 parts by mass, more preferably 0.1 parts by mass to 5 parts by mass, even more preferably 0.1 parts by mass to 3 parts by mass, still more preferably 0.1 parts by mass to 1 part by mass, and particularly preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the specific (meth)acrylic polymer (A). When the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 0.05 parts by mass or more relative to 100 parts by mass of the specific (meth)acrylic polymer (A), there is a tendency that a pressure-sensitive adhesive layer can be formed in which the easy peelability at the initial stage of bonding is less likely to be impaired over time. When the content of the isocyanate-based crosslinking agent in the pressure-sensitive adhesive composition of the present disclosure is 10 parts by mass or less relative to 100 parts by mass of the specific (meth)acrylic polymer (A), there is a tendency that a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating can be formed.
[0114] <<Ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A)>> The ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A)] is not particularly limited, but is, for example, preferably 0.001 to 0.1, more preferably 0.001 to 0.08, further preferably 0.001 to 0.05, and particularly preferably 0.001 to 0.03. When the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A) is 0.001 or more, a pressure-sensitive adhesive layer that exhibits better easy peelability at the beginning of lamination tends to be formed. Also, when the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A) is 0.001 or more, a pressure-sensitive adhesive layer that is less likely to lose its easy peelability over time at the beginning of lamination tends to be formed. When the ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) is 0.1 or less, a pressure-sensitive adhesive layer exhibiting higher adhesive strength after heating tends to be formed.
[0115] In the present disclosure, the term "crosslinkable functional group in the crosslinking agent" means a functional group possessed by the crosslinking agent and capable of undergoing a crosslinking reaction with the crosslinkable functional group in the specific (meth)acrylic polymer (A). For example, when the crosslinking agent is an isocyanate-based crosslinking agent, it means an isocyanate group, and when the crosslinking agent is an epoxy crosslinking agent, it means an epoxy group.
[0116] In the present disclosure, the number of moles of a crosslinkable functional group means the total number of moles of all crosslinkable functional groups when there are multiple crosslinkable functional groups.
[0117] The ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A)] can be calculated by the following formulas (1) to (3).
[0118] Number of moles of crosslinkable functional groups in the crosslinker (unit: mmol) = [Content of crosslinkable functional group in crosslinker (unit: mass%) / solid content concentration of crosslinker (unit: mass%) × blend amount of crosslinker [amount as solid content] (unit: g)] / chemical formula weight of crosslinkable functional group (unit: g / mol) × 1000 (1)
[0119] Number of moles of crosslinkable functional groups in specific (meth)acrylic polymer (A) [unit: mmol] = [Content of the structural unit derived from the monomer having a crosslinkable functional group in the specific (meth)acrylic polymer (A) (unit: mass%) / 100 × blend amount of the specific (meth)acrylic polymer (A) (unit: g) / molecular weight of the structural unit derived from the monomer having a crosslinkable functional group (unit: g / mol) × number of crosslinkable functional groups (valence) in the structural unit derived from the monomer having a crosslinkable functional group × 1000] (2)
[0120] Ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the specific (meth)acrylic polymer (A) = Value obtained by formula (1) / Value obtained by formula (2) (3)
[0121] In addition, when the crosslinking agent is a metal chelate-based crosslinking agent, for example, the crosslinkable functional group contained in the specific (meth)acrylic polymer (A) forms a coordinate bond with a central metal in a metal chelate compound that is a metal chelate-based crosslinking agent, and therefore, by replacing the valence of the central metal with the number of functional groups, the number of moles of the crosslinkable functional groups in the crosslinking agent used for calculating the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A) can be obtained. In the present disclosure, for example, since the valence of the central metal in an aluminum chelate compound, which is a metal chelate crosslinking agent, is 3, the aluminum chelate compound can be calculated by replacing it with one having 3 moles of functional groups per mole.
[0122] When the crosslinking agent is a metal chelate crosslinking agent, the molar number of crosslinkable functional groups in the crosslinking agent is calculated by the following calculation formula (4). When the crosslinking agent is a metal chelate crosslinking agent, the ratio of the molar number of crosslinkable functional groups in the crosslinking agent to the molar number of crosslinkable functional groups in the specific (meth)acrylic polymer (A) can be calculated by replacing the value calculated by calculation formula (1) in the above formula (3) with the value calculated by calculation formula (4) below. Number of moles of crosslinkable functional groups in the crosslinker (unit: mmol) = A × B / C × 1000 (4) A = valence of the metal in the metal chelate crosslinker B = amount of metal chelate crosslinking agent (amount as solid content) (unit: g) C = molecular weight of metal chelate crosslinker (unit: g / mol)
[0123] [Organic Solvent] The pressure-sensitive adhesive composition of the present disclosure may contain an organic solvent. When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the coatability can be improved. As the organic solvent, for example, the same organic solvents as those used in the polymerization reaction of the above-mentioned specific (meth)acrylic polymer can be mentioned.
[0124] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, it may contain only one type of organic solvent, or may contain two or more types of organic solvent.
[0125] When the pressure-sensitive adhesive composition of the present disclosure contains an organic solvent, the content of the organic solvent is not particularly limited and can be appropriately set depending on the purpose.
[0126] [Other ingredients] The pressure-sensitive adhesive composition of the present disclosure may contain components other than the components described above (so-called other components) as necessary, provided that the effects of the composition are not impaired. Examples of other components include various additives such as polymers other than the specific (meth)acrylic polymer, crosslinking catalysts, tackifiers, antioxidants, colorants (e.g., dyes and pigments), light stabilizers (e.g., ultraviolet absorbers), and antistatic agents.
[0127] When the pressure-sensitive adhesive composition of the present disclosure contains other components, the contents of the other components can be appropriately set within a range that does not impair the effects of the pressure-sensitive adhesive composition of the present disclosure.
[0128] <Gel fraction after crosslinking> The gel fraction after crosslinking of the pressure-sensitive adhesive composition of the present disclosure (so-called gel fraction of the pressure-sensitive adhesive layer) is not particularly limited, but is, for example, preferably 50 mass% or more, more preferably 50 mass% to 90 mass%, and even more preferably 50 mass% to 85 mass%. The adhesive composition of the present disclosure, when the gel fraction after crosslinking is 50% by mass or more, tends to be able to form an adhesive layer that exhibits better easy peelability at the beginning of lamination. Also, the adhesive composition of the present disclosure, when the gel fraction after crosslinking is 50% by mass or more, tends to be able to form an adhesive layer whose easy peelability at the beginning of lamination is less likely to be impaired over time.
[0129] In the present disclosure, the "gel fraction of the pressure-sensitive adhesive composition after crosslinking" refers to the proportion of solvent-insoluble matter measured using ethyl acetate as an extraction solvent. Specifically, the gel fraction of the pressure-sensitive adhesive composition after crosslinking is measured according to the following (1) to (4). (1) About 0.15 g of the crosslinked adhesive composition (i.e., adhesive layer) is attached to a 250-mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer facing inward to prevent leakage of the gel, to prepare a sample. The mass is then accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) Take out the sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, measure the mass accurately using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).
[0130] <Application> The application of the pressure-sensitive adhesive composition of the present disclosure is not particularly limited. The pressure-sensitive adhesive composition of the present disclosure exhibits easy releasability at the initial stage of application, and this easy releasability is not easily lost over time. It also exhibits high adhesive strength after heating, and can form a pressure-sensitive adhesive layer that has good compatibility with an adherend, and therefore can be suitably used, for example, for optical components. In particular, the pressure-sensitive adhesive layer formed by the pressure-sensitive adhesive composition of the present disclosure has good compatibility with the adherend, and therefore the pressure-sensitive adhesive layer is unlikely to float or peel off even when the adherend is a display having a curved shape, an optical member having an uneven surface (for example, an optical member including various optical elements such as a prism or a diffraction grating), etc. Thus, the pressure-sensitive adhesive composition of the present disclosure is suitable for, for example, bonding a display having a curved shape and an optical member, bonding a display and an optical member having an uneven surface, and bonding optical members at least one of which has an uneven surface.
[0131] [Adhesive sheet] The pressure-sensitive adhesive sheet of the present disclosure includes a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure. The pressure-sensitive adhesive sheet of the present disclosure has an adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure as described above, and therefore exhibits easy releasability at the initial stage of application, and this easy releasability is not easily lost over time. After heating, the pressure-sensitive adhesive sheet exhibits high adhesive strength and has good compatibility with the adherend. The adherend of the pressure-sensitive adhesive sheet of the present disclosure is not particularly limited, but is preferably, for example, a display having a curved shape and an optical member having an uneven surface (for example, an optical member having various optical elements such as a prism or a diffraction grating). Even when attached to such an adherend, the pressure-sensitive adhesive sheet of the present disclosure is unlikely to cause lifting or peeling of the pressure-sensitive adhesive layer.
[0132] The pressure-sensitive adhesive sheet of the present disclosure may be a substrate-free pressure-sensitive adhesive sheet that does not have a substrate, or a substrate-containing pressure-sensitive adhesive sheet that has a pressure-sensitive adhesive layer on one or both sides of a substrate. In the pressure-sensitive adhesive sheet of the present disclosure, the exposed surface of the pressure-sensitive adhesive layer may be protected by a release film.
[0133] The release film is not particularly limited as long as it can be easily peeled off from the pressure-sensitive adhesive layer, and examples include resin films that have been surface-treated with a release agent on one or both sides (so-called easy-peeling treatment). An example of the resin film is a polyester film, typically a polyethylene terephthalate (PET) film. Examples of the release agent include silicone-based release agents (eg, silicone), wax-based release agents (eg, paraffin wax), and fluorine-based release agents (eg, fluorine-based resins). The release film protects the surface of the pressure-sensitive adhesive layer until the pressure-sensitive adhesive sheet is put to practical use, and is peeled off at the time of use.
[0134] The thickness of the pressure-sensitive adhesive layer is not particularly limited, but is generally from 1 μm to 100 μm, preferably from 3 μm to 50 μm, and more preferably from 5 μm to 30 μm.
[0135] In the present disclosure, the "thickness of the pressure-sensitive adhesive layer" means the average thickness of the pressure-sensitive adhesive layer. The average thickness of the pressure-sensitive adhesive layer is a value measured by the following method. The arithmetic mean value of the thicknesses of the adhesive layer measured at 10 randomly selected points in the thickness direction of the adhesive layer is calculated, and the obtained value is regarded as the average thickness of the adhesive layer. The thickness of the adhesive layer is measured using a film thickness meter.
[0136] When the pressure-sensitive adhesive sheet of the present disclosure includes a substrate, the substrate is not particularly limited. Examples of the substrate include films containing resins such as polyolefin resins (e.g., polyethylene and polypropylene), polyester resins (e.g., polyethylene terephthalate (PET)), acetate resins (e.g., triacetyl cellulose resin), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine-based resins.
[0137] The surface of the substrate on which the adhesive layer is provided may be subjected to a surface treatment such as corona discharge treatment or plasma discharge treatment (so-called adhesion enhancing treatment) in order to improve adhesion between the substrate and the adhesive layer.
[0138] The substrate may contain various additives, such as plasticizers, colorants (eg, dyes and pigments), heat stabilizers, light stabilizers, antistatic agents, flame retardants, antioxidants, and the like. The substrate may be partially or entirely patterned.
[0139] The thickness of the substrate is not particularly limited, but is generally 10 μm to 500 μm, preferably 10 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 10 μm to 100 μm.
[0140] "Substrate thickness" in this disclosure means the average thickness of the substrate. The average thickness of the substrate is a value measured by a method conforming to the above-mentioned method for measuring the average thickness of the pressure-sensitive adhesive layer.
[0141] [How to make adhesive sheets] The method for producing the pressure-sensitive adhesive sheet of the present disclosure is not particularly limited. The pressure-sensitive adhesive sheet of the present disclosure can be produced by known methods. The pressure-sensitive adhesive sheet of the present disclosure can be produced, for example, by the following method. In the case of a substrate-free type adhesive sheet, first, the adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film.Then, the formed coating film is dried to form an adhesive film on the release film.Then, the exposed surface of the formed adhesive film is laminated and attached to the easy-release treated surface of a separately prepared release film, and then cured to produce a substrate-free type adhesive sheet having a laminated structure of release film / adhesive layer / release film.
[0142] In the case of a substrate-type adhesive sheet, first, the adhesive composition of the present disclosure is applied to the easy-adhesion treated surface of the substrate to form a coating film on the substrate. Then, the formed coating film is dried to form an adhesive film on the substrate. Then, the exposed surface of the formed adhesive film is laminated on the easy-release treated surface of the release film, and then cured to produce a substrate-type adhesive sheet having a laminated structure of release film / adhesive layer / substrate.
[0143] As another method, for example, the following method can be mentioned. The adhesive composition of the present disclosure is applied to the easy-release treated surface of a release film to form a coating film on the release film. The formed coating film is then dried to form an adhesive film on the release film. The exposed surface of the formed adhesive film is then laminated to the easy-adhesion treated surface of a substrate, and then cured to produce a substrate-type adhesive sheet having a laminated structure of substrate / adhesive layer / release film.
[0144] The method for applying the pressure-sensitive adhesive composition is not particularly limited. Examples of methods for applying the pressure-sensitive adhesive composition include known methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, knife coater, spray coater, bar coater, applicator, and the like. The amount of the adhesive composition to be applied is not particularly limited, and is appropriately set depending on, for example, the thickness of the adhesive layer to be formed.
[0145] The method for drying the coating film is not particularly limited. Examples of methods for drying the coating film include natural drying, heat drying, hot air drying, and vacuum drying. The drying temperature and drying time of the coating film are not particularly limited, and are appropriately set depending on the thickness of the coating film, the amount of the organic solvent in the coating film, and the like. An example of the drying conditions is drying using a hot air dryer at 70° C. to 120° C. for 30 to 180 seconds.
[0146] The curing is carried out, for example, for 2 to 7 days in an environment with an atmospheric temperature of 20° C. to 50° C. and a relative humidity of 45% to 55% (ie, 45% RH to 55% RH).
[0147] [Optical components] The optical member of the present disclosure includes a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure. The optical member of the present disclosure has a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present disclosure described above, and therefore exhibits easy releasability at the initial stage of attachment, and this easy releasability is not easily lost over time. After heating, the optical member exhibits high adhesive strength and has good compatibility with the adherend. The adherend for the optical member of the present disclosure is not particularly limited, but is preferably, for example, a display having a curved shape and another optical member having an uneven surface (for example, another optical member having various optical elements such as a prism, a diffraction grating, etc.). Even when bonded to such an adherend, the optical member of the present disclosure is unlikely to cause lifting or peeling of the pressure-sensitive adhesive layer.
[0148] The optical member is not particularly limited, and examples thereof include members constituting devices such as image display devices and input devices (so-called optical devices) and members used in these devices. Specific examples of optical components include polarizing plates, AG (Anti-Glare) polarizing plates, wave plates, retardation plates including 1 / 2, 1 / 4 and other wave plates, viewing angle compensation films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflection films, transparent conductive films such as ITO (Indium-Tin Oxide) films, prism sheets, lens sheets, and diffusion plates. Examples of materials for optical components include polyolefin resins (e.g., polyethylene resins and polyester resins), acetate resins (e.g., triacetyl cellulose resins), polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, acrylic resins, vinyl chloride resins, ABS (Acrylonitrile Butadiene Styrene) resins, and fluorine resins. EXAMPLES
[0149] The pressure-sensitive adhesive composition and the like of the present disclosure will be described in more detail below with reference to examples. The present disclosure is not limited to the following examples as long as it does not deviate from the gist of the disclosure.
[0150] [Production of (meth)acrylic polymer A] [Manufacturing example A-1] A reactor equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 116.0 parts by mass of ethyl acetate (organic solvent for polymerization). Next, 100.0 parts by mass of a monomer mixture consisting of 93.0 parts by mass of n-butyl acrylate (n-BA) and 7.0 parts by mass of 2-hydroxyethyl acrylate (2HEA) was prepared in another container. 20% by mass of the prepared monomer mixture was charged into the reactor, and then heated and refluxed at reflux temperature for 10 minutes. Next, under reflux temperature conditions, the remaining 80% by mass of the monomer mixture, 45.0 parts by mass of ethyl acetate (organic solvent for polymerization), and 0.026 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) [ABVN; polymerization initiator] were successively dropped into the reactor over 120 minutes, and the reaction was allowed to proceed for 30 minutes after the completion of the dropping, completing the reaction. After completion of the reaction, the solution was diluted with ethyl acetate so that the solid content concentration became 32.0% by mass, thereby obtaining a solution of (meth)acrylic polymer A-1.
[0151] The term "solids concentration" used herein means the mass proportion of the (meth)acrylic polymer A-1 in the solution of the (meth)acrylic polymer A-1. The same applies to each of the solutions of the (meth)acrylic polymers A-2 to A-6 described below.
[0152] [Manufacturing examples A-2 to A-6] In Production Examples A-2 to A-6, the monomer composition of the (meth)acrylic polymer was changed to the monomer composition shown in Table 1, and the weight average molecular weight of the (meth)acrylic polymer was adjusted to the weight average molecular weight shown in Table 1 by adjusting at least one of the amount of the organic solvent used and the amount of the polymerization initiator used. Except for this, the same operation as in Production Example A-1 was performed to obtain solutions of (meth)acrylic polymers A-2 to A-6 each having a solid content concentration of 32.0 mass%.
[0153] The monomer compositions (unit: mass%) of the (meth)acrylic polymers A-1 to A-6, the glass transition temperatures (Tg, unit: °C) of the (meth)acrylic polymers A-1 to A-6, and the weight average molecular weights (Mw, unit: 10,000 (in the table, "×10") of the (meth)acrylic polymers A-1 to A-6 are shown. 4" are shown in Table 1.
[0154] The glass transition temperatures of the (meth)acrylic polymers A-1 to A-6 were calculated in the same manner as the above-mentioned calculation method for the glass transition temperature of the specific (meth)acrylic polymer (A). The weight average molecular weights of the (meth)acrylic polymers A-1 to A-6 were measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.
[0155] Of the (meth)acrylic polymers A-1 to A-6 obtained above, the (meth)acrylic polymers A-1 to A-4 correspond to the specific (meth)acrylic polymer (A) in the present disclosure.
[0156] [Table 1]
[0157] Details of each monomer listed in Table 1 are as follows. <(Meth)acrylic acid alkyl ester monomer> "n-BA" n-butyl acrylate "MA" Methyl acrylate "2EHA" 2-Ethylhexyl acrylate <Monomers having crosslinkable functional groups> "2HEA" 2-Hydroxyethyl acrylate [Cross-linkable functional group: hydroxyl group, molecular weight: 116] "AA" acrylic acid [Crosslinkable functional group: carboxy group, molecular weight: 72]
[0158] In Table 1, "-" in the monomer composition column means that the monomer in that column was not used.
[0159] [Production of (meth)acrylic copolymer B] [Manufacturing example B-1] A reaction apparatus equipped with a stirrer, a reflux condenser, a successive dropping device, and a thermometer was charged with 45.0 parts by mass of ethyl acetate (organic solvent for polymerization). Next, in another container, a solution consisting of 45.0 parts by mass of methyl methacrylate (MMA), 25.0 parts by mass of n-butyl methacrylate (n-BMA), 29.0 parts by mass of ethyl acrylate (EA; glass transition temperature when homopolymerized is −27° C.), 1.0 parts by mass of a monomer having an organosiloxane skeleton [trade name: KF-2012, number average molecular weight: 5400, manufactured by Shin-Etsu Chemical Co., Ltd.], 0.4 parts by mass of 2,2′-azobis(isobutyric acid) dimethyl [polymerization initiator], and 35.0 parts by mass of ethyl acetate (organic solvent for polymerization) was prepared. The prepared solution was successively dropped into the reaction apparatus over 180 minutes under reflux temperature conditions, and after the end of the dropping, the reaction was allowed to proceed for 180 minutes, and the reaction was completed. After completion of the reaction, the solution was diluted with ethyl acetate to a solid content of 48.0% by mass, to obtain a solution of (meth)acrylic copolymer B-1.
[0160] The term "solid content concentration" used herein means the mass proportion of the (meth)acrylic copolymer B-1 in the solution of the (meth)acrylic copolymer B-1. The same applies to each of the solutions of the following (meth)acrylic copolymers B-2 to B-22.
[0161] [Manufacturing examples B-2 to B-22] In Production Examples B-2 to B-22, the monomer composition of the (meth)acrylic copolymer was changed to the monomer composition shown in Table 2, and the weight average molecular weight of the (meth)acrylic copolymer was adjusted to the weight average molecular weight shown in Table 2 by adjusting at least one of the amount of organic solvent used and the amount of polymerization initiator used. Except for this, the same operation as in Production Example B-1 was performed to obtain solutions of (meth)acrylic copolymers B-2 to B-22 each having a solid content concentration of 48.0 mass%.
[0162] The monomer compositions (unit: mass%) of the (meth)acrylic copolymers B-1 to B-22, the number average molecular weights (Mn) of the monomers having an organosiloxane skeleton in the (meth)acrylic copolymers B-1 to B-22, and the weight average molecular weights (Mw, unit: 10,000 (in the table, "×10") of the (meth)acrylic copolymers B-1 to B-22 4 " are shown in Table 2.
[0163] The number average molecular weights of the monomers having an organosiloxane skeleton in the (meth)acrylic copolymers B-1 to B-22 were calculated in the same manner as the number average molecular weight of the monomers having an organosiloxane skeleton in the specific (meth)acrylic copolymer (B) described above. The weight average molecular weights of the (meth)acrylic copolymers B-1 to B-22 were measured by the same method as the method for measuring the weight average molecular weight of the specific (meth)acrylic polymer (A) described above.
[0164] Of the (meth)acrylic copolymers B-1 to B-22 obtained above, the (meth)acrylic copolymers B-1 to B-10 correspond to the specific (meth)acrylic copolymer (B) in the present disclosure.
[0165] [Table 2]
[0166] Details of each monomer listed in Table 2 are as follows. <(Meth)acrylic monomer> "MMA": Methyl methacrylate [Glass transition temperature when homopolymerized: 103°C] "n-BMA": n-butyl methacrylate [Glass transition temperature when homopolymerized: 21°C] "MA": Methyl acrylate [Glass transition temperature when homopolymerized: 5°C] "2EHMA": 2-Ethylhexyl methacrylate [Glass transition temperature when homopolymerized: -10°C] "EA": Ethyl acrylate [Glass transition temperature when homopolymerized: -27°C] "n-BA": n-butyl acrylate [Glass transition temperature when homopolymerized: -57°C]
[0167] <Monomer having an organosiloxane skeleton> "KF-2012" (product name, number average molecular weight: 5400, compound represented by formula (1), manufactured by Shin-Etsu Chemical Co., Ltd.) "X-22-2426" (trade name, number average molecular weight: 13800, compound represented by formula (1), manufactured by Shin-Etsu Chemical Co., Ltd.) "FM-0711" [Product name: Silaplane (registered trademark) FM-0711, number average molecular weight: 1200, manufactured by JNC Corporation]
[0168] In Table 2, "-" in the monomer composition column means that the monomer in that column was not used.
[0169] [Preparation of Adhesive Composition] Example 1 100 parts by mass (solid content equivalent) of the solution of the (meth)acrylic polymer A-1, 8 parts by mass (solid content equivalent) of the solution of the (meth)acrylic copolymer B-1, and 0.4 parts by mass (solid content equivalent) of a crosslinking agent [product name: Takenate (registered trademark) D-110N, xylylene diisocyanate (XDI) compound, solid content concentration: 75% by mass, manufactured by Mitsui Chemicals, Inc.] were thoroughly mixed to obtain a pressure-sensitive adhesive composition of Example 1. In the obtained pressure-sensitive adhesive composition, the ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1 [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1] was 0.025.
[0170] The ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the (meth)acrylic polymer A-1 was calculated in the same manner as the ratio of the number of moles of the crosslinkable functional groups in the crosslinking agent to the number of moles of the crosslinkable functional groups in the specific (meth)acrylic polymer (A). Specifically, it was calculated as follows. Note that Takenate (registered trademark) D-110N, which is an isocyanate-based crosslinking agent, has a solid content of 75% by mass and an isocyanate group content of 11.5% by mass. The chemical formula weight of the isocyanate group is 42. The molecular weight of the constituent unit derived from 2-hydroxyethyl acrylate, which is a monomer having a crosslinkable functional group, is 116.
[0171] Calculation formula (1) Number of moles of crosslinkable functional groups in the crosslinker (unit: mmol) = Content of crosslinkable functional group in crosslinker (unit: mass%) / Solid content of crosslinker (unit: mass%) × Blend amount of crosslinker [amount as solid content] (unit: g) / Chemical formula amount of crosslinkable functional group (unit: g / mol) × 1000 =11.5(mass%) / 75(mass%)×0.4(g) / 42(g / mol)×1000=1.46≒1.5
[0172] Calculation formula (2) Molar number of crosslinkable functional groups in (meth)acrylic polymer A-1 [unit: mmol] = [Content of constitutional units derived from monomers having crosslinkable functional groups in (meth)acrylic polymer A-1 (unit: mass%) / 100×amount of (meth)acrylic polymer A-1 (unit: g) / molecular weight of constitutional units derived from monomers having crosslinkable functional groups (unit: g / mol)×number of crosslinkable functional groups in constitutional units derived from monomers having crosslinkable functional groups (valence)×1000] =[7.0(mass%) / 100×100(g) / 116(g / mol)×1×1000]=60.34≒60.3
[0173] Calculation formula (3) Ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1 (i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A-1) = Value calculated using formula (1) / Value calculated using formula (2) =1.5 / 60.3=0.0248 ≒ 0.025
[0174] [Examples 2 to 18] The same procedure as in Example 1 was carried out except that the formulation of the adhesive composition in Example 1 was changed to the formulation shown in Table 3, to obtain each of the adhesive compositions of Examples 2 to 18.
[0175] [Comparative Examples 1 to 17] The same procedure as in Example 1 was carried out except that the formulation of the adhesive composition in Example 1 was changed to the formulation shown in Table 4, to obtain each of the adhesive compositions of Comparative Examples 1 to 17.
[0176] The compositions of the pressure-sensitive adhesive compositions of Examples 1 to 18 and Comparative Examples 1 to 17, and the ratio of the number of moles of crosslinkable functional groups in the crosslinking agent to the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A [i.e., the number of moles of crosslinkable functional groups in the crosslinking agent / the number of moles of crosslinkable functional groups in the (meth)acrylic polymer A] are shown in Tables 3 and 4.
[0177] [Table 3]
[0178] [Table 4]
[0179] Details of the crosslinking agents listed in Table 3 and / or Table 4 are as follows. "XDI" [Product name: Takenate (registered trademark) D-110N, xylylene diisocyanate compound (adduct of xylylene diisocyanate (XDI) and trimethylolpropane (TMP)), isocyanate group content: 11.5% by mass, solid content: 75% by mass, manufactured by Mitsui Chemicals, Inc.] "TDI" [Product name: Coronate (registered trademark) L-45E, tolylene diisocyanate compound (adduct of tolylene diisocyanate (TDI) and trimethylolpropane (TMP)), isocyanate group content: 7.9% by mass, solid content: 45% by mass, manufactured by Tosoh Corporation] "HMDI" [Product name: Sumidur (registered trademark) N75, hexamethylene diisocyanate compound (biuret of hexamethylene diisocyanate (HMDI)), isocyanate group content: 16.5% by mass, solid content: 75% by mass, manufactured by Sumika Covestro Urethane Co., Ltd.] "Aluminum chelate" [Aluminum chelate A (trade name, chemical name: aluminum tris(acetylacetonate), molecular weight: 324) manufactured by Kawaken Fine Chemical Co., Ltd. was diluted with acetylacetone and ethyl acetate, solids concentration: 3.24% by mass] The above "Takenate," "Coronate," and "Sumidur" are all registered trademarks.
[0180] In Tables 3 and 4, the values shown in the "blended amount" column are all values calculated as solid content. In Table 4, "-" means that the ingredient in that column was not included.
[0181] [Preparation of adhesive sheets for evaluation] The adhesive composition prepared above was applied to the easy-adhesion treated surface of a polyethylene terephthalate (PET) film [trade name: Teijin (registered trademark) Tetoron (registered trademark) film, model number: G2P2, thickness: 50 μm, manufactured by Teijin Film Solutions Co., Ltd.] so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C and a drying time of 1 minute, forming an adhesive film on the PET film. Next, the surface on which the adhesive film was exposed was laminated on the release treated surface of a release film [trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.] that had been easily peeled with a separately prepared silicone-based release treatment agent, and then the film was left to stand for 4 days in an environment of an atmospheric temperature of 23 ° C and 50% RH to be aged, and an evaluation adhesive sheet was prepared. The prepared pressure-sensitive adhesive sheet for evaluation had a laminated structure of release film / pressure-sensitive adhesive layer / PET film.
[0182] [Measurement and Evaluation] 1. Gel fraction The gel fraction after crosslinking (i.e., the gel fraction of the pressure-sensitive adhesive layer) was measured using the pressure-sensitive adhesive composition prepared above. Specifically, it was measured by the following method. The adhesive composition was applied to the release-treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated for easy peeling with a silicone-based release treatment agent, so that the thickness after drying was 20 μm, forming a coating film. Next, the formed coating film was dried using a hot air circulation dryer under drying conditions of a drying temperature of 100 ° C. and a drying time of 1 minute, forming an adhesive film on the release film. Next, the exposed surface of the adhesive film was laminated on the release-treated surface of a release film (trade name: Film Byna (registered trademark) 100E-0010 No. 23, thickness: 100 μm, manufactured by Fujimori Kogyo Co., Ltd.) that had been treated for easy peeling with a separately prepared silicone-based release treatment agent, and then left to stand for 4 days in an environment of an atmospheric temperature of 23 ° C. and 50% RH to be aged, to produce a non-substrate type adhesive sheet. The pressure-sensitive adhesive sheet thus produced had a laminated structure of release film / pressure-sensitive adhesive layer / release film.
[0183] The gel fraction of the pressure-sensitive adhesive layer peeled off from the obtained pressure-sensitive adhesive sheet was measured according to the following (1) to (4). The results are shown in Tables 5 and 6. (1) About 0.15 g of the adhesive layer is attached to a 250 mesh wire net (100 mm x 100 mm) whose mass has been accurately measured using a precision balance, and the wire net is folded five times with the attached adhesive layer on the inside to prevent the gel from leaking out, to prepare a sample. After that, the mass is accurately measured using a precision balance. (2) The obtained sample is immersed in 80 mL of ethyl acetate for 3 days. (3) Take out the sample, wash it with a small amount of ethyl acetate, and dry it at 120°C for 24 hours. Then, measure the mass accurately using a precision balance. (4) Calculate the gel fraction using the following formula. Gel fraction (unit: mass%) = (ZX) / (YX) x 100 where X is the mass of the wire mesh (unit: g), Y is the mass of the wire mesh with the adhesive layer attached before immersion (unit: g), and Z is the mass of the wire mesh with the adhesive layer attached after immersion and drying (unit: g).
[0184] 2. Adhesive strength (1) Initial adhesive strength The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was laminated on the surface of a polyimide (PI) sheet [trade name: Kapton (registered trademark) 100H, manufactured by Toray DuPont Co., Ltd.] (hereinafter simply referred to as "PI") laminated to a stainless steel (so-called SUS) plate, and then pressed by moving a 2 kg roller back and forth once to prepare a test piece X-1. The prepared test piece X-1 was left to stand for 30 minutes in an environment of an atmospheric temperature of 23°C and 50% RH. After leaving the test piece X-1 stationary, the adhesive sheet piece for evaluation (structure: adhesive layer / PET film) was peeled off from the PI at 180° in the long side (150 mm) direction to measure the adhesive strength (unit: N / 25 mm) using a single column material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the pressure-sensitive adhesive layer exhibited easy peelability at the initial stage of bonding.
[0185] -Evaluation criteria- A: The adhesive strength is 0.01N / 25mm or more and less than 0.40N / 25mm. B: The adhesive strength is 0.40N / 25mm or more and less than 1.00N / 25mm. C: The adhesive strength is 1.00N / 25mm or more.
[0186] (2) Adhesive strength after aging The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was laminated on the surface of the PI laminated to the SUS plate, and then a 2 kg roller was moved back and forth once to press the surface, and test piece X-2 was prepared. The prepared test piece X-2 was left to stand for 24 hours in an environment with an atmospheric temperature of 23°C and 50% RH. After leaving the test piece X-2 stationary, the adhesive sheet piece for evaluation (structure: adhesive layer / PET film) was peeled off from the PI at 180° in the long side (150 mm) direction to measure the adhesive strength (unit: N / 25 mm) using a single column type material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the adhesive layer was one whose easy peelability at the initial stage of bonding was unlikely to deteriorate over time.
[0187] -Evaluation criteria- A: The adhesive strength is 0.01N / 25mm or more and less than 1.10N / 25mm. B: The adhesive strength is 1.10N / 25mm or more and less than 1.50N / 25mm. C: The adhesive strength is 1.50N / 25mm or more.
[0188] (3) Adhesive strength after heating The adhesive sheet for evaluation prepared above was cut to a size of 25 mm x 150 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was laminated on the surface of the PI laminated to the SUS plate, and then a 2 kg roller was moved back and forth once to press the two pieces together to prepare a test piece X-3. The prepared test piece X-3 was left in a dryer set at a temperature of 50°C for 20 minutes, then removed from the dryer and left in an environment with an atmospheric temperature of 23°C and 50% RH for 30 minutes. After leaving the test piece X-3 stationary, the adhesive sheet piece for evaluation (structure: adhesive layer / PET film) was peeled off from the PI at 180° in the long side (150 mm) direction to measure the adhesive strength (unit: N / 25 mm) using a single column material testing machine (model: STA-1225) manufactured by A&D Co., Ltd., under conditions of an atmospheric temperature of 23°C, 50% RH, and a peeling speed of 300 mm / min. Evaluation was then performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the adhesive layer exhibited high adhesive strength after heating.
[0189] -Evaluation criteria- A: The adhesive strength is 9.00N / 25mm or more. B: The adhesive strength is 7.00N / 25mm or more and less than 9.00N / 25mm. C: The adhesive strength is less than 7.00N / 25mm.
[0190] 3.Familiarity The adhesive sheet for evaluation prepared above was cut into a size of 100 mm x 100 mm to prepare an adhesive sheet piece for evaluation. The release film was peeled off from the prepared adhesive sheet piece for evaluation (composition: release film / adhesive layer / PET film), and the surface of the adhesive layer exposed by peeling was attached to PI from the center, and the time until the adhesive completely wetted and spread on the PI due to natural gravity was measured. If the entire surface of the adhesive layer was in close contact with the PI, it was determined that the adhesive had completely wetted and spread on the PI. The adhesion was judged by visual observation. Then, evaluation was performed according to the following evaluation criteria. The results are shown in Tables 5 and 6. If the evaluation result was "A" or "B", it was determined that the pressure-sensitive adhesive layer had good compatibility with the adherend.
[0191] -Evaluation criteria- A: The time it takes for the entire surface of the adhesive layer to adhere to the PI is within 20 seconds. B: The time it takes for the entire surface of the adhesive layer to adhere to the PI is 21 to 39 seconds. C: It takes 40 seconds or more for the entire surface of the pressure-sensitive adhesive layer to adhere to the PI, or the entire surface of the pressure-sensitive adhesive layer does not adhere to the PI.
[0192] [Table 5]
[0193] [Table 6]
[0194] As shown in Table 5, it was confirmed that the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 18 exhibited easy releasability to the adherend at the beginning of application, that this easy releasability was not easily lost over time, and that they exhibited high adhesive strength after heating. It was also confirmed that the pressure-sensitive adhesive layers formed from the pressure-sensitive adhesive compositions of Examples 1 to 18 had good compatibility with the adherend.
[0195] On the other hand, as shown in Table 6, it was confirmed that the adhesive layers formed with the adhesive compositions of Comparative Examples 1 to 17 showed results inferior to the adhesive layers formed with the adhesive compositions of the Examples in at least one of the evaluations of easy peelability at the beginning of lamination, easy peelability over time after lamination, adhesive strength after heating, and compatibility with the adherend.
Claims
1. A (meth)acrylic polymer (A) containing a structural unit derived from a monomer having a crosslinkable functional group and having a glass transition temperature of less than 0°C; a (meth)acrylic copolymer (B) containing 0.1% by mass to 10% by mass of structural units derived from a monomer having an organosiloxane skeleton, based on all structural units, and 25% by mass to 45% by mass of structural units derived from a (meth)acrylic monomer having a glass transition temperature in the range of −30° C. or higher and lower than 10° C. when made into a homopolymer, the copolymer having a glass transition temperature of 20° C. to 50° C. and a weight average molecular weight of 40,000 to 400,000; A cross-linking agent; Including, the crosslinkable functional group is at least one of a hydroxyl group and a carboxy group, the number average molecular weight of the monomer having an organosiloxane skeleton in the (meth)acrylic copolymer (B) is in the range of 4,000 or more and less than 20,000; The pressure-sensitive adhesive composition, wherein the content of the (meth)acrylic copolymer (B) is 0.1 to 21 parts by mass based on 100 parts by mass of the (meth)acrylic polymer (A).
2. The pressure-sensitive adhesive composition according to claim 1 , wherein the monomer having an organosiloxane skeleton is a compound represented by the following formula (1): 【Chemistry 1】 In formula (1), R 1 represents a hydrogen atom or a methyl group, R 2 represents a monovalent organic group. m and n each independently represent 0 or an integer of 1 or more, provided that m and n are not 0 at the same time.
3. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1 or 2.
4. An optical member comprising a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to claim 1 or 2.
Citation Information
Patent Citations
Adhesive composition, adhesive layer and adhesive sheet
JP2017203164A
Adhesive sheet
JP2020026483A
Adhesive composition and adhesive sheet
JP2020050716A
Adhesive composition and adhesive sheet
JP2020050717A
Silicone graft copolymer, adhesive composition and adhesive tape
JP2020143248A